'I swim like a frog that has lost the use of its hind legs': The Pursuit of Health and Leisure in Buxton, 1781‐90. (8th May 2017) - Collinge, Peter
Abstract: As the eighteenth century progressed, the number of spa resorts proliferated; so too did an elaborate range of leisure options associated with them. Such was the extent of these offerings that the therapeutic qualities of the waters have a tendency to be overlooked in assessments of spa culture as the century drew to a close. Using Hester Newdigate's correspondence and Jane Macartney's accounts relating to Buxton, Derbyshire, this article examines the extent to which the reputation and perceived benefits of a resort's waters determined the choice of destination and the significance of hydropathic regimens during visitors' repeat visits.